A Dietary Antioxidant Formulation Ameliorates DNA Damage Caused by γ-Irradiation in Normal Human Bronchial Epithelial Cells In Vitro - J. P. Jose Merlin; Sabateeshan Mathavarajah; Graham Dellaire; Kieran P. J. Murphy; H. P. Vasantha Rupasinghe (MDPI AG, 2022)
Antioxidants can be used as radioprotectants to reduce DNA damage due to exposure to radiation that could result in malignancies, including lung cancer. Mortality rates are consistently higher in lung cancer, which is usually diagnosed at later stages of cancer development and progression. In this preliminary study, we examined the potential of an antioxidant formulation (AOX2) to reduce DNA damage using a cell model of human normal bronchial epithelial cells (BEAS-2B). Cells were exposed to γ-irradiation or smoke-related hydrocarbon 4[(acetoxymethyl)nitrosamino]-1 (3-pyridyl) 1-butanone (NNKOAc) to induce DNA damage. We monitored intracellular reactive oxygen species (ROS) levels and evidence of genotoxic damage including DNA fragmentation ELISA, γ-H2AX immunofluorescence, and comet assays. Pre-incubation of the cells with AOX2 before exposure to γ-irradiation and NNKOAc significantly reduced DNA damage. The dietary antioxidant preparation AOX2 significantly reduced the induction of the tumor suppressor protein p53 and DNA damage-associated γ-H2AX phosphorylation by radiation and the NNKOAc treatment. Thus, AOX2 has the potential to act as a chemoprotectant by lowering ROS levels and DNA damage caused by exposure to radiation or chemical carcinogens.